Pengaruh Social Media Marketing terhadap Brand Trust Hotel Pangeran City Padang - Rukmana, Vira Hardiyanti; Abrian, Youmil (ARZUSIN, 2023)
This study aims to determine the effect of social media marketing on the brand trust of the Prince City Padang Hotel. In this study, researchers used quantitative research methods by conducting an online survey of Instagram followers at the Prince City Padang Hotel, totaling 184 samples. The method used in sampling is non probability sampling with purposive sampling technique. The analysis technique used in this research is validity test, reliability test, quantitative descriptive analysis, assumption test (normality test, linearity test, and coefficient of determination test). The results of this study indicate that social media marketing has a positive and significant effect on brand trust. By looking at the beta value in the unstandardized coefficients column which is 0.874 and the t test it is known that the calculated t value is 6,282 which is greater than the t table with 1.658. The R square value is 0.615, meaning that 61.5% of brand trust that occurs can be explained by social media marketing variables.